Thermal Performance Analysis of Compact Heat Exchangers for Thermoelectric Generators (Journal of Engineering, 2020)
The efficiency of internal combustion engines (ICE) is usually about thirty percent of the total energy of the fuel. The residual energy is lost in the exhaust gas, the lubrication, and the cooling water in the radiators. Recently much of the researcher’s efforts have focused on taking advantage of wasted energy of the exhaust gas. Using a thermoelectric generator (TEG) is one of the promising ways. However, TEG depends entirely on the temperature difference, which may be offered by the exhaust muffler. An experimental test has been conducted to study the thermal performance of a different muffler internal design. The researchers resort to the use of lost energy in an ICE using TEG, which is one of the ways to take advantage of energy lost, which depends on the difference in temperature. TEG needs a heat exchanger and the muffler one of its types. In this work, four different types of mufflers will be designed and studied.  The results showed that the thermal performances of the studied models compared to the empty cavity were as follows, the serial plate structure 56.11%, the central Box structure 52.73%, and the central curvature structure 29.61%. The highest thermal performance is on the serial plate structure relative to the other types.